2022
DOI: 10.1371/journal.pone.0266612
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and well-being among students of health disciplines in Geneva, Switzerland: The importance of academic satisfaction in the context of academic year-end and COVID-19 stress on their learning experience

Abstract: Introduction University students’ psychological health is linked to their academic satisfaction. This study aimed to investigate students’ psychological health and academic satisfaction in the context of COVID-19 and academic year-end stress. Materials and methods Standardized self-filled scales for anxiety, depression, stress, psychological well-being, academic satisfaction (subjective assessment of students’ quality of life in their educational setting), and an ad-hoc scale for stress on the learning exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 48 publications
1
12
0
3
Order By: Relevance
“…Furthermore, our logistic regression model identified risk factors for depression in the nonclinical group, including lower academic satisfaction and poor help-seeking behaviours. These findings are consistent with those of previous research, which demonstrated a significant correlation between lower academic satisfaction and depression (β = −0.26, P < 0.001); 36 they are also consistent with the results of a large-scale national survey that revealed a significant correlation between decreased help-seeking behaviours and depressive symptoms. 37 Moreover, the model showed protective factors against depression in the nonclinical group, including father's parenting attitude and good attendance at school.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, our logistic regression model identified risk factors for depression in the nonclinical group, including lower academic satisfaction and poor help-seeking behaviours. These findings are consistent with those of previous research, which demonstrated a significant correlation between lower academic satisfaction and depression (β = −0.26, P < 0.001); 36 they are also consistent with the results of a large-scale national survey that revealed a significant correlation between decreased help-seeking behaviours and depressive symptoms. 37 Moreover, the model showed protective factors against depression in the nonclinical group, including father's parenting attitude and good attendance at school.…”
Section: Discussionsupporting
confidence: 92%
“…Scientific research emphasizes that higher levels of stress are significantly associated with lower levels of academic satisfaction [ 33 , 82 , 122 , 123 ]. Conversely, higher academic satisfaction is associated with lower levels of depression and anxiety [ 124 ] and stress [ 33 , 123 , 124 ]. Furthermore, the study by Tran et al [ 123 ] shows that academic satisfaction appears to be an important predictor of stress and anxiety.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Podobne wyniki odnotowano również w populacji studentów. Zaobserwowany w badaniach stres nie tylko stanowił źródło zmęczenia i poczucia wypalenia [13], ale także prowadził do gorszych wyników w nauce, co znacząco zmniejszało satysfakcję studentów z aktywności akademickiej [14]. Co więcej, napięcie związane z koniecznością uczestniczenia w zajęciach w formie online, które zyskało już własne określenie technostresu, nie tylko przekładało się na większe poczucie wypalenia i mniejsze zaangażowanie, ale też korelowało z wyższym poziomem kortyzolu [15].…”
Section: Wstępunclassified